Religion, Ethics and Values in terms of Spirituality (International Journal of Food and Nutritional Sciences, 2022)
Religion and spirituality are the foundation of human life. Spirituality is again culminating in the practice of Advaita Vedanta. The improbable progress of modern science and technology has now stymied man's sense of the necessity of religious observance. As a result, religion and humanity have disappeared from the society. People are uplifted by the welfare of religion and spirituality, morally and humanely universal. But modern physics does not make people religiously and spiritually scientific. Science attracts people only to physical comfort and ease, to the extent that people become indulgent and selfish. As a result, the lack of morality in the society and the international arena threatens the existence of human beings in desperate conflicts and terrorism. The only way to free the society from this conflict and terror is to follow mentioned in the Vedas Dharma. So only if modern science can be integrated with the religion and spirituality of Vedanta, science will be saved from inevitable destruction. Otherwise destruction is inevitable.